Pertanggung Jawaban Direksi dalam Perseroan Terbatas dan Perspektif Hukum Korporasi - Prakasa , Ragil Surya; Farni, Fatimah Hayati; Gusherva , Ramizah Kamelia; Daitu, Apin Rahmat; Aditya, Rizky Bintang (ASOSIASI IDEBAHASA KEPRI, 2024)
A company is a legal entity (rechtspersoon) which is a legal subject other than Humans, like corporate people, can also be subject to rights and obligations, and Just like humans, companies can be held responsible if they are proven to have done something errors and causing losses, including liability for criminal acts. Company In its business activities it certainly does not operate alone, there is a management who is the